Autophagy Benefits the Replication of Egg Drop Syndrome Virus in Duck Embryo Fibroblasts - Wang, Xueping; Qi, Xuefeng; Yang, Bo; Chen, Shuying; Wang, Jingyu (Frontiers in Microbiology, 2018)
Egg drop syndrome virus (EDSV) is an economically important pathogen with a broad host range, and it causes disease that leads to markedly decreased egg production. Although EDSV is known to induce apoptosis in duck embryo fibroblasts (DEFs), the interaction between EDSV and its host needs to be further researched. Here, we provide the first evidence that EDSV infection triggers autophagy in DEFs through increases in autophagosome-like double-membrane vesicles, the conversion of LC3-I to LC3-II, and LC3 colocalization with viral hexon proteins. Conversely, P62/SQSTM1 degradation, LC3-II turnover, and colocalization of LAMP and LC3 confirmed that EDSV infection triggers complete autophagy. Furthermore, we demonstrated that inhibition of autophagy by chloroquine (CQ) and 3-methyladenine (3MA) or RNA interference targeting ATG-7 decreased the yield of EDSV progeny. In contrast, induction of autophagy by rapamycin increased the EDSV progeny yield. In addition, we preliminaryly demonstrated that the class I phosphoinositide 3-kinase (PI3K)/Akt/mTOR pathway contributes to autophagic induction following EDSV infection. Altogether, these finding lead us to conclude that EDSV infection induces autophagy, which benefits its own replication in host cells. These findings provide novel insights into EDSV-host interactions.